Awareness of Arizona's immigration law SB1070 predicts classroom behavioural problems among Latino youths during early adolescence. Issue 9 (15th July 2018) - Santos, Carlos E.; Menjívar, Cecilia; VanDaalen, Rachel A.; Kornienko, Olga; Updegraff, Kimberly A.; Cruz, Samantha
ABSTRACT: Bridging diverse areas of inquiry (i.e. legal studies and developmental psychology), this study explored the longitudinal association between Latina/o youths' burgeoning legal consciousness, measured as awareness of Senate Bill 1070 (SB1070) in Arizona, and their adjustment in school, measured as classroom regulatory behaviours, and examined whether this association varied across immigrant generational status and gender. Participants were 689 Latina/o middle school students in Arizona ( Mage  = 12.06 years, SD  = .98). Multiple regression analysis revealed a significant interaction between Latina/o youths' awareness of SB1070 at Time 1 and gender in predicting classroom regulatory behaviours at Time 2 (controlling for levels of it at Time 1). Males who were higher on awareness of SB1070 at Time 1 reported lower levels of classroom regulatory behaviours at Time 2. This study underscores the importance of measuring youths' awareness of laws and how this awareness may impact their academic adjustment.